A customização do Moodle tendo como base maior navegabilidade e usabilidade do ambiente: uma experiência de ensino - Ficiano, Antonio Marcos (2010)
The research work - which is characterized by the intervention - aims to understand and analyze the overall process of building an interface to the Moodle Learning Management System, assuming the combination of three elements: navigability, usability and architecture information seeking to encourage learning, which demonstrates the process of building the interface to highlight the importance of multidisciplinary work. The project addresses the Distance Education and the concept, characteristics and possibilities of interactivity of AVAs, with a brief mention of multimedia, the Internet and its history. Speaks of computer languages, programming techniques, classification of languages, types of software, models of virtual environments and web-based methodologies to software development, based on the approach to systems design. This is the Moodle platform, with its technological potential, examining the process of customizing the platform with an corporate course, in which greater navigability and usability have been taken as the base. And finish the job search when he observes the product built under the light of the concepts and theories studied, and how to apply these principles could be confirmed in promoting effective learning. Research has shown that both teachers and students are benefited by participating in classes to distance learning in virtual environments, while it is well structured, in that they enable the development of critical thinking, practical reasoning, ease of interaction, collaboration and socializing